Association between changes in genital immune markers and vaginal microbiome transitions in bacterial vaginosis - Philipp Foessleitner; Briah Cooley Demidkina; Wafae El-Arar; Miles Goldenberg; Meena Murthy; Agnes Bergerat; Ofri Bar; Douglas S. Kwon; Caroline M. Mitchell (Scientific Reports)
Abstract Bacterial vaginosis (BV), characterized by an imbalance in the vaginal microbiota, is a prevalent condition among women of reproductive age and a risk factor for human immunodeficiency virus, sexually transmitted infections, and preterm birth. BV is generally considered to induce mucosal inflammation, but the specific pathways and cell types involved are not well characterized. This prospective study aimed to assess associations between microbial changes and mucosal immune responses in BV patients. Therefore, samples from 20 premenopausal women with BV and treated with metronidazole were analyzed. Vaginal swabs, menstrual cup, and endocervical cytobrush samples were collected before treatment, weekly for four weeks, and at 2, 4, and 6 months for Nugent scoring, immune cell populations and cytokine analysis. Of 105 study intervals, 27 (25.7%) showed improvement in Nugent category, 61 (58.1%) remained unchanged, and 17 (16.2%) worsened. Improvement correlated with decreased monocytes (p = 0.005), while worsening was linked to increased monocytes (p < 0.001) and dendritic cells (p = 0.02). B cells (p = 0.02) and IFN-γ-induced chemokines - IP-10 (p = 0.007), MIG (p = 0.049), and ITAC (p = 0.005) - were associated with improvement. In conclusion, although the T-cell-associated chemokines IP-10, ITAC, and MIG were strongly associated with improvements in Nugent category, our findings indicate that antigen-presenting cells, particularly monocytes, show the most dynamic response to shifts in the vaginal microbiota in patients with BV.